1991
DOI: 10.1507/endocrj1954.38.309
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Acute Pseudogout Attack following Parathyroidectomy.

Abstract: Two cases of acute attack of pseudogout associated with primary hyperparathyroidism are reported. Case 1 suffered from acute pain and swelling of the right ankle and dorsal of the right foot. Case 2 suffered from unknown fever and pain of the bilateral jaw, shoulder, elbow, wrist and knee joints. Postoperative radiological studies revealed the association of chondrocalcinosis in both cases. Synovial fluid in case 2 was aspirated and analyzed for calcium pyrophosphate dihydrate crystal by microscopic examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…Pseudogout commonly a b c It has been suggested that pseudogout is caused by abnormal increases in blood calcium concentrations due to hyperparathyroidism or in tissue iron concentrations due to haemochromatosis, or by abnormal decreases in blood magnesium concentrations in conditions such as hypomagnesaemia. 6 However, because a majority of pseudogout patients have no history of these metabolic diseases, the involvement of genetic factors is still possible. As with synovial chondromatosis, pseudogout also commonly affects the knee joint as well as other large joints, including the elbow, wrist and hip joints, [6][7][8] but rarely affects the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudogout commonly a b c It has been suggested that pseudogout is caused by abnormal increases in blood calcium concentrations due to hyperparathyroidism or in tissue iron concentrations due to haemochromatosis, or by abnormal decreases in blood magnesium concentrations in conditions such as hypomagnesaemia. 6 However, because a majority of pseudogout patients have no history of these metabolic diseases, the involvement of genetic factors is still possible. As with synovial chondromatosis, pseudogout also commonly affects the knee joint as well as other large joints, including the elbow, wrist and hip joints, [6][7][8] but rarely affects the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serum calcium changes acutely following parathyroidectomy, which has a well recognized association with pseudogout. 2 These elevated levels, with or without changes in the matrix which promote crystal formation, are thought to lead to the formation of calcium pyrophosphate dihydrate crystals in cartilage. This is substantiated by recent research 14 on the mouse 'ank' gene, which has implicated a specific gene on chromosome 15 in the pathogenesis of CPPD crystal deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Each crystal deposit is associated with a different clinical syndrome, and each are relatively rare conditions. Calcium pyrophosphate dihydrate (CPPD) deposition disease is a rare, benign condition in which CPPD crystals are deposited in synovial fluid 2 and which results in the calcification of articular cartilage (chondrocalcinosis). This leads to an acute arthritis (or 'pseudogout') in 25% of patients.…”
mentioning
confidence: 99%
“…Развитие псевдоподагры или острого ПФК-ассоциированного артрита также характерно для пациентов с ПГПТ [4], особенно при нормализации кальция сыворотки крови после паратиреоидэктомии [26,27,28], хотя в ряде работ подобной взаимосвязи не наблюдалось [6,18]. Некоторые авторы полагают, что именно резкое снижение уровня кальция, а не абсолютная его величина, является фактором, провоцирующим псевдоподагрическую атаку в послеоперационном периоде [4].…”
Section: болезнь депонирования кристаллов пирофосфата кальцияunclassified